2022
DOI: 10.1007/s00418-022-02152-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis and three-dimensional reconstruction of cellular structures involved in SARS-CoV-2 spread

Abstract: The cytoskeleton not only deals with numerous interaction and communication mechanisms at the cellular level but also has a crucial role in the viral infection cycle. Although numerous aspects of SARS-CoV-2 virus interaction at the cellular level have been widely studied, little has been reported about the structural and functional response of the cytoskeleton. This work aims to characterize, at the ultrastructural level, the modifications in the cytoskeleton of infected cells, namely, its participation in fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous in vitro studies by our group 36 and Baselga et al 48 reported that the virus induces filopodium formation to maximize the infection process. It is also known that viral particles are highly concentrated in this region of filopodia, facilitating contact with the membrane of new cells.…”
Section: Discussionmentioning
confidence: 94%
“…Previous in vitro studies by our group 36 and Baselga et al 48 reported that the virus induces filopodium formation to maximize the infection process. It is also known that viral particles are highly concentrated in this region of filopodia, facilitating contact with the membrane of new cells.…”
Section: Discussionmentioning
confidence: 94%
“…Although many ultrastructural investigations to track the SARS-CoV-2 infection life cycle and effects on cellular organelles have been performed (for instance, see Barreto-Vieira et al 2022 ), little attention has been paid to the role of the cytoskeleton in these processes, though it is known to be involved in replication of other viruses (Foo and Chee 2015 ). To this end, Baselga et al ( 2022 ) have performed a transmission electron microscopic investigation of SARS-CoV-2 infection of Vero E6 cultured cells, with particular attention focused on the role of cytoskeletal elements in virus infection and transmission between neighboring cells. To help ultrastructurally identify the cytoplasmic structures involved in the viral infection and spreading process, the authors cut serial sections from embedded cell cultures, acquired images, and performed three-dimensional reconstructions.…”
Section: Transmission Electron Microscopy To Investigate Sars-cov-2 C...mentioning
confidence: 99%